2007
DOI: 10.1002/ana.21097
|View full text |Cite
|
Sign up to set email alerts
|

Hematoma resolution as a target for intracerebral hemorrhage treatment: Role for peroxisome proliferator‐activated receptor γ in microglia/macrophages

Abstract: PPARgamma in macrophages acts as an important factor in promoting hematoma absorption and protecting other brain cells from ICH-induced damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
414
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(427 citation statements)
references
References 39 publications
9
414
1
3
Order By: Relevance
“…Despite the detrimental effects of CD36 in an acute ischemic setting, CD36-dependent phagocytosis was associated with functional benefit in neonatal stroke [155]. Additionally, the clearing of red blood cells after hemorrhagic stroke was associated with increased CD36 expression and improved functional recovery [156]. This might be related to the role of CD36 in M2 phenotypic switching of mononuclear cells.…”
Section: Inflammation Versus Resolutionmentioning
confidence: 98%
“…Despite the detrimental effects of CD36 in an acute ischemic setting, CD36-dependent phagocytosis was associated with functional benefit in neonatal stroke [155]. Additionally, the clearing of red blood cells after hemorrhagic stroke was associated with increased CD36 expression and improved functional recovery [156]. This might be related to the role of CD36 in M2 phenotypic switching of mononuclear cells.…”
Section: Inflammation Versus Resolutionmentioning
confidence: 98%
“…Phagocytosis of several particulate Ags, such as RBC and apoptotic cells, is enhanced by PPAR-␥ agonists in microglia and macrophages (38,39,49). However, the ability of PPAR-␥ agonists to modulate bacterial phagocytosis by microglia has not yet been investigated.…”
Section: S Aureus Phagocytosis By Microglia Is Enhanced By Ciglitazonementioning
confidence: 99%
“…We have also demonstrated that PPAR-γ agonists in vitro reduce production of proinflammatory mediators and free radicals produced during phagocytosis. Finally, PPAR-γ agonists in vivo demonstrate the ability to protect other brain cells from the secondary injury induced in a mouse model of ICH [102]. These data suggest that PPAR-γ in macrophages acts as an important factor in promoting hematoma absorption and protecting other brain cells from ICH-induced damage and may represent a promising therapeutic target in the management of ICH [103].…”
Section: Pharmacologic Hematoma Clearancementioning
confidence: 82%
“…Pre-clinical work in our laboratory demonstrates that peroxisome proliferators-activated receptor-gamma (PPAR-γ) agonists promote hematoma resolution, decrease neuronal damage, and improve functional recovery in a mouse model of ICH [102]. We have also demonstrated that PPAR-γ agonists in vitro reduce production of proinflammatory mediators and free radicals produced during phagocytosis.…”
Section: Pharmacologic Hematoma Clearancementioning
confidence: 93%